An Empirical Study of the Determinants of Foreign Investment in China: A Western Australian Perspective - Liu, Yi (Routledge, 2010)
The literature, regarding the determinants of inward foreign direct investment (FDI) in China, emphasizes national or regional inward FDI, and largely depends on secondary data. This study reports findings from the analysis of primary data provided by 43 managers of Western Australian companies that are either operating or planning to invest in China reveals market size, labor cost, and business ethics were important factors for promoting foreign investment to the Chinese marketplace; while gender, organizational size, and networking have potential to play a significant mediating role in investment decisions. These exploratory observations are a departure point for further investigations.